Thermographic methodologies used in infrastructure inspection: A review—Post-processing procedures. (15th May 2020) - Garrido, I.; Lagüela, S.; Otero, R.; Arias, P.
Highlights: By now, Non-Destructive techniques (NDTs) are the best to infrastructure inspection. InfraRed Thermography (IRT) is one of the best NDTs to infrastructure inspection. Exhaustive review of the most recent and important IRT post-acquisition procedures. Qualitative and quantitative modes are the typical IRT post-acquisition approaches. Robustness of IRT to face the greatest challenges in infrastructure inspection. Abstract: The different thermal behaviour between defects and unaltered zones allows the detection and thermal characterisation of superficial, and subsuperficial defects, which must be considered when maintaining a structure in optimal conditions. InfraRed Thermography is among the most appropriate Non-Destructive techniques to measure these thermal behaviours, represented on temperature maps of the infrastructure analysed by thermal images, regardless the size of the structure. In addition, InfraRed Thermography is also used for the thermal characterisation of structures for such important purposes as the energy study of buildings. Proof of the importance of InfraRed Thermography in infrastructure inspections are the continuous developments of new thermal image processing algorithms, where the post-processing stage is widely used to improve the inspection performance. In this work, an exhaustive review is performed regarding the most recent and important practical thermographic procedures for infrastructure applications, focusing on the post-acquisition stage, due to the lack of an in-depth analysis regarding the most recent and used algorithms. Specifically, the theory of these thermal image processing techniques is described, classifying them according to the corresponding theoretical post-acquisition approach used: qualitative and/or quantitative analysis. In addition, a discussion based on the advantages and disadvantages of each thermal data processing technique is performed, as well as a description of the latest IRT works related to each. Ending with a series of conclusions, this review paper confirms the maturity of InfraRed Thermography to face the greatest challenges in infrastructure inspection, although it also mentions the limitations to overcome and the future trends to follow.